Comparison of the effectiveness of zero-profile device and plate cage construct in the treatment of one-level cervical disc degenerative disease combined with moderate to severe paraspinal muscle degeneration - Abudouaini, Haimiti; Xu, Hui; Yang, Junsong; Yi, Mengbing; Lin, Kaiyuan; Wang, Sibo (Frontiers in Endocrinology, 2023)
Objective: To investigate the disparities in clinical outcomes, radiological findings, and complications between two frequently utilized anterior cervical surgical procedures. The objective is to offer guidance for the management of cervical paraspinal muscle degeneration (PMD) in conjunction with cervical disc degenerative disease (CDDD). Methods: A total of 140 patients who underwent single-level ACDF at our department were included in this study. The patients were divided into three groups based on the severity of PMD: mild (n=40), moderate (n=54), and severe (n=46), as determined by Goutalier fat infiltration grade. The subjects of interest were those with moderate-severe PMD, and their clinical outcomes, radiological parameters, and complications were compared between those who received a stand-alone zero-profile anchored cage (PREVAIL) and those who received a plate-cage construct (PCC). Results: The JOA, NDI, and VAS scores exhibited significant improvement at all postoperative intervals when compared to baseline, and there were no discernible differences in clinical outcomes between the two groups. While the PCC group demonstrated more pronounced enhancements and maintenance of several sagittal alignment parameters, such as the C2-7 angle, FSU angle, C2-7 SVA, and T1 slope, there were no statistically significant differences between the two groups. The incidence of dysphagia in the zero-profile group was 22.41% at one week, which subsequently decreased to 13.79% at three months and 3.45% at the final follow-up. In contrast, the plate cage group exhibited a higher incidence of dysphagia, with rates of 47.62% at one week, 33.33% at three months, and 11.90% at the final follow-up. Notably, there were significant differences in the incidence of dysphagia between the two groups within the first three months. However, the fusion rate, occurrence of implant subsidence, and adjacent segment degeneration (ASD) were comparable at the final follow-up. Conclusion: Although no significant disparities were observed between these two technologies in terms of complications such as adjacent segment degeneration and implant subsidence, the zero-profile technique exhibited superior performance over PCC in relation to dysphagia during the early stages of postoperative recovery. To validate these findings, studies with longer follow-up periods and evaluations of multilevel cervical muscles are warranted.